Enhancing Mentally Retarded Students’ Comprehension: The Development of MASH Project-Based Reading Material - Lulu Asyrifah (ELLITE, 2017)
The development of reading material through Project Based Learning (PBL)strategy using MASH is aimed to meet mentally retarded students’ learning andtarget needs in EFL English reading courses. This study employed a researchand development design which comprises seven stages, namely: a) students’need analysis, design of MASH Project based reading, development, expertvalidation, implementation, reading material evaluation, and final product inthe form of MASH project based reading material. The result of the reading material development took resulted six chapters in terms of number 11-20, expression agree/disagree, and part of house where containing material of thetopic, video, and exercises that utilize Project-Based Learning strategy. Theresult of experts’ validation from an English teacher who assessed the materialrevealed the score was 78% that sorted out into ‘very good’ category and anInformatics teacher who assessed the media revealed the score was 74% thatsorted out into ‘good’ category. While, the result of the students’ responserelated to the product showed the total score was 79% that the students agreewith MASH media to be used in learning process. As its effectiveness towardthe improvement of mentally retarded students’ reading comprehension is notmeasured yet, so an experimental study is addressed for further research tomeet the issue of MASH reading material effectiveness and conduct the similarproject with another media to develop more reading materials and activities.